Evaluating the distribution of water resources in western Canada using synoptic climatology and selected teleconnections. Part 1: winter season. Issue 14 (11th June 2014) - Newton, Brandi W.; Prowse, Terry D.; Bonsal, Barrie R.; Carey, Sean; Quinton, Bill
Abstract The Climatic Redistribution of western Canadian Water Resources project was designed to identify regions of increased/decreased water availability by evaluating a suite of atmospheric, hydroclimatic and streamflow variables. This research component focuses on the atmospheric drivers of air temperature and precipitation in the watersheds originating on the leeward slopes of the Rocky Mountains. Dominant winter (November–April) synoptic‐scale mid‐tropospheric circulation patterns from 1950 to 2011 are classified using self‐organizing maps, and frequency distributions for positive/negative phases of the Southern Oscillation Index (SOI), Pacific Decadal Oscillation (PDO) and Arctic Oscillation are statistically compared. Corresponding high‐resolution gridded temperature and precipitation anomalies are calculated for each synoptic type, and spatial patterns of above/below‐average temperature and precipitation and north/south gradients are identified. Gridded 6‐month values of the Standardized Precipitation–Evapotranspiration Index are also used to categorize winters into regions of high/low snowpack. Results indicate high‐pressure ridges over the Pacific Ocean (western North America), and low‐pressure troughs over western North America (Pacific Ocean) are associated with anomalously cool (warm) and wet (dry) conditions in the study region. Several statistically different synoptic type frequencies were found for positive/negative phases of the SOI, PDO and Arctic Oscillation. Most notably, positive (negative) phases of the SOI and negative (positive) phases of the PDO are associated with a higher (lower) frequency of ridging over the Pacific Ocean (western North America). Through improved knowledge of the relationships between teleconnections, mid‐tropospheric circulation and surface climate, the spatial and temporal distribution of water resources in western Canada is better understood. Copyright © 2014 John Wiley & Sons, Ltd.